2019
DOI: 10.1002/cjce.23509
|View full text |Cite
|
Sign up to set email alerts
|

One‐step solvothermal synthesis of hollow Bi2WO6 photocatalyst

Abstract: A one‐step solvothermal synthesis of hollow microspherical Bi2WO6 nanophotocatalyst was carried out for the first time under the collective action of potassium chloride (KCl) and polyvinylpyrrolidone (PVP). The physicochemical properties such as crystal structure, morphology, specific surface area, and optical properties of the material were characterized by means of XRD, SEM, EDS, UV‐vis, and BET. The effect of KCl and PVP on the morphology control of the product is discussed. Rhodamine B dye in wastewater wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…[8][9][10] A lot of literatures have shown that doping of nonmetallic elements such as F, Br, I, C, N, and S can effectively enhance the photocatalytic performance of BiOCl semiconductors. [11][12][13][14][15][16][17] Solid solution photocatalyst is different from simple element doping, which forms a new impurity energy level to reduce the bandgap. The solid solution photocatalyst reduces the band gap by designing the electronic structure of photocatalyst, that is, to adjust the position of valence band or conduction band.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] A lot of literatures have shown that doping of nonmetallic elements such as F, Br, I, C, N, and S can effectively enhance the photocatalytic performance of BiOCl semiconductors. [11][12][13][14][15][16][17] Solid solution photocatalyst is different from simple element doping, which forms a new impurity energy level to reduce the bandgap. The solid solution photocatalyst reduces the band gap by designing the electronic structure of photocatalyst, that is, to adjust the position of valence band or conduction band.…”
Section: Introductionmentioning
confidence: 99%